The Experiences of Left-Behind Fathers: Breaking the Traditional Filipino Paternal Roles in Parenting - Gutierrez, Joselito (Universitas Negeri Surabaya, 2024)
Many societies, including those in the Philippines, subscribe to the traditional concept that the father's essential responsibilities are being the provider and protector of his family. In Filipino parenting, fathers are providers for the family's economic needs while mothers are responsible for nurturing. More women are migrating to work abroad, leaving fathers to assume all primary parenting roles as providers, protectors, and nurturers. This has created a new family dynamic in recent years.This research paper explores Filipino fathers' experiences with a wife working abroad. Using an Interpretative Phenomenological Analysis (IPA), the researcher interviewed some employed fathers to reveal how they accepted, adapted, and made sense of the family set up as they simultaneously fulfilled the roles of both the father and mother to their children. Research revealed that when the mother left to work abroad, the father embraced their role in caring for their children. Filipino fathers are open to reversing traditional parenting roles. Although some fathers still let their wives take care of the children, many have become the primary caregivers. Parenting alone has helped them understand the importance of being involved in their children's upbringing